2018
DOI: 10.1161/circresaha.118.311207
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement Strategies for Cardiac Regenerative Cell Therapy

Abstract: The idiom heart of the matter refers to the focal point within a topic and, with regard to health and longevity, the heart is truly pivotal for quality of life. Societal trends worldwide continue toward increased percent body fat and decreased physical activity with coincident increases in chronic diseases including cardiovascular disease as the top global cause of death along with insulin resistance, accelerated aging, cancer. Although long-term survival rates for cardiovascular disease patients are grim, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 98 publications
(112 reference statements)
0
20
0
Order By: Relevance
“…Over the past decade, pioneering preclinical research into the use of cell therapy for cardiac regeneration has been completed [20]. However, cell therapy remains challenging for a number of reasons including the selection of cell types, the minimal potency of injected cells, and the limited engraftment and retention of administered cells [20][21][22]. A recent study demonstrated that although transplanted, cells could not differentiate into cardiac myocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, pioneering preclinical research into the use of cell therapy for cardiac regeneration has been completed [20]. However, cell therapy remains challenging for a number of reasons including the selection of cell types, the minimal potency of injected cells, and the limited engraftment and retention of administered cells [20][21][22]. A recent study demonstrated that although transplanted, cells could not differentiate into cardiac myocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Upon transplantation, the stem cells are confronted with a harsh environment at the MI site, which results in a lower engraftment rate, poor survival, and weak proliferative abilities, therefore limiting the effectiveness of the therapy [ 33 ]. The in vitro preconditioning of stem cells aims to prepare the cells for the ischemic environment prior to transplantation and is among the possible solutions that have demonstrated significant enhancement in infarction site recovery [ 34 , 35 ]. The cells can be preconditioned via various methods, including but not limited to pretreatment with hypoxia, drugs, biological agents, and growth factors ( Figure 1 ) [ 31 , 36 , 37 ].…”
Section: Stem Cell Preconditioning For MI Treatmentmentioning
confidence: 99%
“…SCASCs generated from bone marrow are known as bone-marrow SCs, 37 having clinical significance in restoring damaged cardiac tissue through gene therapy. 70 Also, they can be a potential source for auto-HSCT.. 37 There is an improvement in GVHD in patients with bone-marrow SC transplantation compared to peripheral blood SCs (PBSCs). 19 Bone marrow–SC transplantation is utilized in various hematologic malignancies, such as AML, ALL, and CML.…”
Section: Bone-marrow Stem Cells As Source For Stem-cell Transplantatimentioning
confidence: 99%